2010
DOI: 10.1089/scd.2009.0254
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic Effect of Hepatocyte Growth Factor-Expressing Mesenchymal Stem Cells in Small-for-Size Liver Transplant Rats

Abstract: Ischemia-reperfusion and chronic injuries associated with small-for-size liver transplantation (SFSLT) impair the regeneration of liver graft and induce liver fibrosis. Mesenchymal stem cells (MSCs) can prevent the development of liver fibrosis, and hepatocyte growth factor (HGF) can also attenuate liver cirrhosis. Our previous studies have demonstrated that higher occurrence of liver fibrosis existed in rats post-SFSLT, and that implantation of HGF/MSCs, the human HGF (hHGF)-expressing MSCs, can improve liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 45 publications
3
56
0
Order By: Relevance
“…Recent studies demonstrate that HGF reduces fibrogenesis by not only inhibiting TGF-b signalling but also down-regulating TGF-b in several experimental models of fibrosis [10,15,49,51,52]. In the present study, the production of TGF-b1 was downregulated after apoptotic cell instillation during the late fibrotic phases (days 14 and 21 after bleomycin), while the HGF production continuously increased and peaked at 21 days, indicating that the antifibrotic action in the BLM+ApoJ group is concordant with an increase in HGF and a decrease in TGF-b1 levels as compared with the BLM+Sal group.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrate that HGF reduces fibrogenesis by not only inhibiting TGF-b signalling but also down-regulating TGF-b in several experimental models of fibrosis [10,15,49,51,52]. In the present study, the production of TGF-b1 was downregulated after apoptotic cell instillation during the late fibrotic phases (days 14 and 21 after bleomycin), while the HGF production continuously increased and peaked at 21 days, indicating that the antifibrotic action in the BLM+ApoJ group is concordant with an increase in HGF and a decrease in TGF-b1 levels as compared with the BLM+Sal group.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from IL-10, HGF is a major contributor to reduced fibrosis, which has been shown to be effective in advancing clean wound healing in a variety of tissues such as liver 94 and various skin contexts. 95,96 HGF has also been attributed to chronic wounds, with differential regulation of HGF production and presence of c-Met in chronic wound dermis.…”
Section: Reduction In Scar Formationmentioning
confidence: 99%
“…Moreover, HGF enhanced the incorporation of MSCs into injured livers, and the engrafted cells and their progeny produced albumin [55]. In another study the same group showed that HGF-expressing MSCs significantly inhibited the formation of liver fibrosis in rats undergoing small-for-size rat LT with synergistic effects of the MSCs and HGF [56].…”
Section: Animal Studiesmentioning
confidence: 93%
“…56.6 Mesenchymal stromal cell administration in solid organ transplantation 56.6.1 Kidney transplantation Kidney transplantation is the best option for patients suffering from end-stage kidney diseases, improving survival and quality of life compared with maintenance dialysis [28,29]. The site of placement of a transplanted kidney is shown in Figure 56.1.…”
Section: Prevention Of Ischemia-reperfusion Injurymentioning
confidence: 99%